センジョウ ジュウリョクケイ NIPRORI-1 カタ ノ センジョウ ニ オケル セイノウ シケン - 瀬川, 爾朗; セガワ, ジロウ; 春日, 隆; カスガ, タカシ; 神沼, 克伊; カミヌマ, カツタダ; Segawa, Jiro; Kasuga, Takashi; Kaminuma, Katsutada (1982)
P(論文) 1980年に新しく製作した船上重力計NIPRORI-1型の性能試験のため, 同年9月から10月にかけて砕氷船「ふじ」の内地巡航に同乗した。この試験により, NIPRORI-1型重力計が南極で使用するに足る十分な性能を保有することが確かめられた。 A surface ship gravity meter NIPRORI-1 which was built in 1980 was tested on board the icebreaker FUJI during her cruise around the Japanese Islands from September to October 1980. This test has verified that performance of the new gravity meter is satisfactory as a device to be used for the measurement in the Antarctic region. departmental bulletin paper